Thermal Characteristics of Lattakia Governorate during the Period 1990-2020 - Riad Qara Fallah; Aya Alwaraa (African Journal of Advanced Pure and Applied Sciences, 2022)
Temperature is the essential element for understanding and analyzing climatic characteristics in any region, and in order to understand temperature behavior in Lattakia Governorate, it was studied during the climatic cycle between 1990-2020 through mathematical and statistical evidence and indicators based on statistical programs Excel2019, Spss26 and ArcGis10.5 geographic information systems , where the values of the coefficient of variation (did not exceed 5%) revealed the lack of variation and dispersion of the annual mean of temperature from the average period of the study, and the equation of the general trend showed the trend of this climatic element towards a significant increase by 1.3°C, in addition to recording a significant seasonal temperature rise at 95% confidence level.